2016
DOI: 10.1038/ncomms11726
|View full text |Cite
|
Sign up to set email alerts
|

TRIM31 promotes Atg5/Atg7-independent autophagy in intestinal cells

Abstract: Autophagy is responsible for the bulk degradation of cytosolic constituents and plays an essential role in the intestinal epithelium by controlling beneficial host–bacterial relationships. Atg5 and Atg7 are thought to be critical for autophagy. However, Atg5- or Atg7-deficient cells still form autophagosomes and autolysosomes, and are capable of removing proteins or bacteria. Here, we report that human TRIM31 (tripartite motif), an intestine-specific protein localized in mitochondria, is essential for promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 72 publications
(87 reference statements)
3
73
1
1
Order By: Relevance
“…In ATG5-or ATG7-deficient cells, TRIM31 directly interacts with phosphatidylethanolamine (PE) in a palmitoylation-dependent manner, leading to the induction of autophagy. In this process, the B-box domain of TRIM31 is required for the formation of TRIM31-positive puncta and colocalization with PE [23]. The E3 ubiquitin ligase complex of TRIM28 with its regulators MAGEA3 or MAGEA6 (MAGEA3/6-TRIM28) can target AMPK for ubiquitination and proteasome-mediated degradation, resulting in significantly reduced autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ATG5-or ATG7-deficient cells, TRIM31 directly interacts with phosphatidylethanolamine (PE) in a palmitoylation-dependent manner, leading to the induction of autophagy. In this process, the B-box domain of TRIM31 is required for the formation of TRIM31-positive puncta and colocalization with PE [23]. The E3 ubiquitin ligase complex of TRIM28 with its regulators MAGEA3 or MAGEA6 (MAGEA3/6-TRIM28) can target AMPK for ubiquitination and proteasome-mediated degradation, resulting in significantly reduced autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM proteins participate in multiple cellular processes including cell proliferation, transcriptional regulation, immunity and cancer progression [11][12][13][14]. A series of studies indicated that many TRIM proteins are linked to autophagy [15][16][17][18][19][20][21][22][23][24][25][26][27]. Recently, several studies demonstrated that TRIM proteins can act as both autophagy cargo receptors and platforms assembling autophagosome-formation machinery.…”
Section: Introductionmentioning
confidence: 99%
“…The data that support this conclusion rely on the observation that CQ often produces identical cytotoxicity in cancer cells engineered to lack key autophagy genes compared with their wild-type controls. The concern with this conclusion is that noncanonical autophagy programs such as Rab9-associated (Nishida et al 2009) or TRIM31-associated vesicles (Ra et al 2016) can be recruited in cells deficient in canonical autophagy genes. The presence of these alternative autophagy programs implores caution to the notion that CQ's cytotoxicity must be autophagy-independent.…”
Section: Lysosome Inhibitorsmentioning
confidence: 99%
“…In addition, high expression of TRIM31 was revealed to activate the PI3K/Akt signaling pathway to promote tumor cell proliferation and invasion in gallbladder cancer (30). In intestinal epithelial cells, TRIM31 interacted directly with phosphatidylethanolamine in a palmitoylation-dependent manner, resulting in the formation of autolysosomes and providing a preventable pathway for the study of intestinal pathogen infections (31). Notably, it was revealed that TRIM31 was highly expressed in HCC, and overexpression of TRIM31 could partially abrogate the inhibitory effect of miR-29c-3p on HCC.…”
Section: Discussionmentioning
confidence: 99%